Desenvolvimento de modelo experimental de neuropatia sensitiva periférica induzida pelo agente antineoplásico oxaliplatina em camundongos - Pontes, Renata Bessa (2009)
Oxaliplatin (OXL) is a third-generation platinum-based chemotherapy with broad spectrum of anti-tumoral activity. Exhibt potent cytotoxic activity including against cancer colorectal, ovarian and lung cancer. Among the toxic effects are: laryngospasm, nauseas, vomiting, fatigue and peripheral neuropathy, focus of that work. That research planned to develop an experimental model for study of the peripheral neuropathy induced by OXL in mice that are animal genetically more similar to the human, economic and given the knockout species existence for several factors. The study was approved by the Committee of Ethics in Animal Research of the UFC (protocol nº 70/07). Mice Swiss male (20-40g) were treated with OXL (1-4 mg/kg, EV) for 4 weeks in parallel to the neurophatic tests utilized for evaluate the development of the peripheral neuropathy and Route Rod for verify some motor compromise. To mechanical hyperalgesia and allodynia thermal were evaluated by the test of immersion of the tail (TIC) in cold water (4 or 10ºC) and in water heated (46 or 42ºC). The test of hyperalgesia and allodynia (HPM; Von Frey) consisted of the stimulation of the rear paws with a sensor of force (g) up to his retreat by a movement of "flinch". It was still verified the analgesic action of the carbamezepine (CZP), oxcarbazepine (OZP), gabapentin (GABAP) and indomethacin (INDO) in the TIC cold water. It was carried out to immunohistochemical of the hands paws of the animals in 24h and of 7 to 28 days. The results shows that in the HPM had a significant reduction (p<0,001) in the nociceptive threshold from the 14º day reaching the maximum one in the dose of 2mg/kg compared to the control group. In the TIC 4ºC had a significant reduction (p<0,05) in the nociceptive threshold in the 56º day, in the TIC allodynia by the cold one (10ºC) was observed a significant reduction (p<0,01) in the nociceptive threshold also in the 56º day, in the TIC allodynia by the hot one (42ºC) was observed a significant reduction (p<0,05) in the nociceptive threshold from the 35º day. Those tests reached the maximum one in the dose of 1mg/kg compared with the control group and in the TIC 46ºC was observed a significant reduction (p<0,01) in the nociceptive threshold from the 49º day reaching the maximum one in the doses of 1 and 4mg/kg compared to the control group. In the test Route Rod no significant variation was observed in no of the groups, indicating the absence of motor compromise. The handling with CZP (0,3-30mg/kg), OZP (0,3-100mg/kg) and GABAP (6-54mg/kg) increased the nociceptive threshold, indicating analgesic effect and INDO (1-4mg/kg) did not show analgesic activity in that model. In the analysis of the immunohistochemical was verified that exists the probable participation of SP, CGRP and NMDA peripheral and nitrotyrosine. Therefore, the use of mice and of the different approach of administration of the OXL (EV) can be utilized in future models making feasible the use of the drug for handling of the cancer, mainly the colorectal, with all the therapeutic plan without that to NSP interfere in the activities of the treated patient.